(untitled) (Praxis Educativa, 2018)
This article analyzes the training experiences of indigenous youth who participate in university extension projects developed at the National University of Salta (Salta, Argentina). From an anthropological perspective, the ways in which extension contributes to the university inclusion of these young people are described. The conclusions indicate that university extension is an area that allows them to reinforce their identity belongings as undergraduate students and as members of an indigenous community.